Possible Roles of Micro RNA‑142‑5p and Claudin-1 in Development of Hashimoto’s Thyroiditis in Iraqi Patients - Khaled Nather Taha; Farhan Abood Risan; Abdulameer Jasim Mohammed (Journal of Techniques)
Background: Micro RNA 142-5p may one day be employed as diagnostic or therapeutic targets in the therapy of autoimmune diseases. The expression of microRNA142-5p in serum from newly diagnosed patients with Hashimoto's thyroiditis has only been studied in a few tissue cases. In addition, elevated microRNA142-5p in tissue is associated with reduced Claudin1 tissue expression in thyrocyte HT patients. This study tries to evaluate these findings in serum of HT before starting treatment. Methods: One hundred-twenty subjects enrolled in this study, divided into 40 newly diagnosed HT patients before treatment are classified into (Euthyroid HT, Subclinical HT, and Overt HT) based on thyroid function test presentation, 40 non-immune hypothyroidism, and 40 healthy controls. The possible mechanisms of microRNA-142-5p in Hashimoto's thyroiditis were investigated by measuring serum MicroRNA 142-5p by quantitative RT-PCR, in addition, to measuring serum Claudin1 by sandwich ELISA. Results: At the time of presentation, the outcome of the tests revealed that 12.5 percent of HT patients had euthyroidism, 30 percent had overt thyroiditis, and 57.5 percent had sub-clinical thyroiditis. miR-142-5p, that's been found to be expressed at significant levels in HT patient serum. Moreover, the ELISA test demonstrated serum Claudin1 was no significant difference between the studied groups. Conclusions: Our data suggest that micro RNA 142-5p may play a role in HT development and pathogenesis through an as-yet-unidentified mechanism, even though serum Claudin1 is not significantly affected in the serum of HT. Chemical thyroid function characteristics at the time of HT manifestation in adults are mostly influenced by the age of the patients and gender.